Real-world versus clinical trial CAR T outcomes among patients diagnosed with diffuse large B-cell lymphoma. Issue 28 (1st October 2022) - McBride, Kaitlyn; Snyder, Sophie
Abstract : 413 Background: Chimeric antigen receptor (CAR) T cell therapy is a high-value innovative therapy for patients diagnosed with diffuse large B cell lymphoma (LBCL). The Federal Drug Administration (FDA) has approved three CAR T-cell therapies for these patients: axicabtagene ciloleucel, tisagenlecleucel and liso-cel. Data on real-world survival and adverse events (AEs) among Medicare beneficiaries receiving CAR T is limited. This study aims to compare real-world CAR T outcomes to clinical trial results. Methods: Retrospective cohort analysis using CMS 100% Medicare Fee-for-Service (FFS) Inpatient (Part A) and Outpatient (Part B) claim files. The database contains information on inpatient and outpatient diagnoses based on the International Classification of Diseases 10th Revision-Clinical Modification (ICD-10-CM). Inpatient files were used to identify Medicare FFS beneficiaries with LBCL diagnosis (ICD-10-CM code C83.3) who received inpatient CAR T procedure between January 2020 and March 2021. Demographic characteristics (age & sex), 12-month survival, and AEs were identified and compared to outcomes from three CAR T clinical trials (tisagenlecleucel: JULIET; axicabtagene ciloleucel (axi-cel): ZUMA-1; and lisocabtagene maraleucel (liso-cel): TRANSCEND NHL 001). Results: The real-world cohort (RW pts) consisted of 463 Medicare FFS beneficiaries with LBCL who were administered CAR T cell therapy inpatient between January 2020 and March 2021. A higher proportion of RW pts were aged 65 or older compared to clinical trial patients, and a lower proportion of RW pts were male (57% vs 65%). Overall, fewer RW pts experienced cytokine release syndrome (CRS) and anaemia compared to patients across the clinical trials (Table). Other common AEs, including neutropenia, fatigue, and thrombocytopenia, occurred at lower rates among RW pts compared to rates in the axicabtagene ciloleucel and liso-cel clinical trials. Survival at 12-months was comparable between RW pts and clinical trial patients. Conclusions: Study findings suggest that real-world occurrence of common AEs following inpatient CAR T administration, including CRS and anaemia, are lower compared to clinical trial outcomes. Real-world evidence of CAR T is critical for understanding real-world benefit, safety, and value of novel therapies. Clinical Trials Real-World All-Grade AEs Tisagenlecleucel 1 Axi-cel 2 Liso-cel 3 Medicare FFS Patients 111 111 267 463 ≥65 years 23% 22% 42% 90% Sex male NR 65% 65% 57% Survival (12 months) 49% 59% 58% 59% Cytokine release syndrome (CRS) 58% 93% 42% 26% Neutropenia 20% 84% 63% 40% Anaemia 48% 66% 48% 31% Fatigue 25% 51% 44% 29% Thrombocytopenia 13% 58% 41% 32% Hypokalemia 23% 33% 19% 33% 1 Schuster et al., 2019 (JULIET); 2 Neelapu et al., 2017 (ZUMA-1); 3 Abramson et al., 2020 (TRANSCEND NHL 001)